Anger;it's impact on human body - PRAKASH KUMAR YADAV; RAM LOCHAN YADAV; Khatri Sapkota, Niraj (Innovare Journal Health Sciences, 2017)
Anger is one of our most powerful and vital emotions with behavioural manifestation. It is described as an intense feeling in response to frustration , hurt, disappointment, or threatening.The benefits of anger include overcoming fears and building confidence to counter dangerous phenomenon  or threats which leads to the fight or flight response while the disadvantages of anger consist of excess anger serving as a numbing agent emotionally, physically and cognitively.Physiologically, emotions is considered to commence  from  brain nucleus named as  amygdale , part of brain   responsible for identifying threats to our well-being, and  relaying out an alarm when threats are identified that result in taking steps to protect ourselves. It is important to recognize the physiological effects of anger especially with all the damage this emotion might produce to our body system.This review article examines the physiology, causes of anger and impact of anger on the body.